船上救生设备用绞车及传动部件的设计计算 - 秦钢 (Jixie chuandong)
The basic structure,working principles and main features of the winch used in ship life-saving appliances are introduced.The strength calculation and verification of major parts are carried outto insure the winch operating safely and reliably.